Experimental study of through the wall imaging for the detection of vital life signs using SFWR - Pardhu Thottempudi; Vijay Kumar (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Now a day’s defence applications associated to novel, army and military war fields are required wall imaging discrimination. As of now many wallimaging techniques are designed but didn’t identify the vital signs behind walls with accurate working. Therefore, a novel advance wall image tracking method is required identification of human target. An experimental study on through the wallimaging (TWI) to detect the life signs using sweep frequency continuous wave radar (SFCWR) is explained in this paper. The proposed system consists of agilent vector network analyzer (VNA) (Agilent E5071B ENA), horn antenna and a computer. The information of heart beat and the breathing can be a shift identification routine was used to collect information from the back scattering electric current. The outcomes of the procedure give the information of heart beat and breathing signs of real human being.